Principal's Leadership Strategy in Efforts to Development the Quality of Human Resources in Schools - Dacholfany, Muhammad Ihsan; Iqbal, Muhammad; Rahmi, Elvi; Purwanto, Muhammad Bambang (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The principle plays a crucial role in enhancing the human resources in schools. This is so that well-performing school leaders may create solutions-based policies that address issues that arise in schools. In an endeavor to improve the caliber of human resources, this is what prompted the researcher to bring up the subject of the principal's leadership strategy. This study used qualitative research approaches and interview-based data collection. Three resource people, including administrators, teachers, and principals, were interrogated. This study's data analysis method involves providing data, reducing it, and then making conclusions from it. The principal of Pagar Dewa Elementary School faces a number of challenges in trying to improve the caliber of the school's human resources, including a large number of senior teachers, inadequate infrastructure and facilities, and a remote location from urban areas. However, the principal of SD Pagar Dewa, Macan Sakti District, Musi Banyuasin Regency implemented a number of strategies to improve the quality of the school's human resources. These included establishing discussion rooms, enforcing rewards and sanctions, and providing teachers with training and direction so they could develop into professional educators and be able to keep up with the times.